PKM KELOMPOK SISWA BERBASIS TEKNOLOGI INFORMASI (IT) - Intyaswati, Drina; Hapsari, Dian Tri (Universitas Esa Unggul, 2018)
AbstractWriting is a postive activity that needs to be developed since childhood. Currently there are many writing competitions among children or school students. Many writing contest on the blog, which is a combination of writing and utilization of information technology. However, there are still many Indonesian children who still do not have a habit of writing, because of this reason, PKM team UPN